THE EFFECTIVENESS OF COMPETENCY-BASED TRAINING PROGRAM CLASSES ON HUMAN RESOURCES PERFORMANCE IN THE CREATIVE INDUSTRY SECTOR - Farawowan, Fauziah F.; Hardianti, Andi (PT. Hafasy Dwi Nawasena, 2025)
This study aims to analyze the effectiveness of competency-based training on the performance of human resources (HR) in the creative industry sector using the Systematic Literature Review (SLR) approach. The analysis was conducted on 50 recent studies (2020–2025) selected from 947 initial articles through the stages of identification, selection, and quality assessment. The results of the study show that competency-based training consistently has a positive impact on creativity (92.9%), innovation (93.3%), competitiveness (88.9%), and productivity (86.4%). The effectiveness of the program is influenced by the design of the relevant curriculum, the integration of digital technologies (e-learning, VR/AR), collaboration between industry and educational institutions, and the support of organizational management. These findings also have global implications in supporting the Sustainable Development Goals (SDGs) agenda, especially in the aspects of quality education (SDG 4), decent work and economic growth (SDG 8), and industrial innovation (SDG 9). However, this study found a research gap, namely the limitations of longitudinal studies on long-term impacts, the lack of studies on the integration of cutting-edge technologies such as artificial intelligence and machine learning, and the need for a more systematic industry-education collaboration model. Thus, this study emphasizes that competency-based training is a key strategy in strengthening the competitiveness of creative industry human resources in the era of global digital transformation.